PEMBINAAN PRODUK OLAHAN KERUPUK KEMPLANG IKAN LELE DENGAN MICROWAVE PADA POHLAKSAR RULE ATHALLA BANYUASIN - Guttifera Guttifera; Selly Ratna Sari; Siti Lestari; Rizki Eka Puteri; Prastiyo Wibowo (Jurnal Abdi Insani, 2023)
Catfish is one of fish has a complete nutritional content, especially a high content of amino acids such as leucine and lysine. This South Sumatra is area has many typical foods, especially snacks, one of which is fish crackers. UMKM Kemplang, especially poklasar Rule Athallah, which is located in Talang Kelapa, Banyuasin Regency, has processed food in the of catfish kemplang crackers and usually in the process of processing it is fried twice to produce better results. This community activity purposed to improve the quality of catfish kemplang cracker products in the Rule Athallah poklasar that uses a microwave. This community was carried out at the Athallah Banyuasin Rule poklasar. The activities carried out by the team are training, mentoring and monitoring to partners. The activity carried out during the training was attended by 38 participants consisting of members of the Rule Athallah poklasar and students. This community also produces superior products of microwave catfish kemplang crackers with more complex nutritional content.